2012
DOI: 10.1016/j.cub.2012.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Mammalian Primary Cilia

Abstract: Summary The primary cilium is a microtubule-based organelle that senses extracellular signals as a cellular antenna [1]. Primary cilia are found on many types of cells in our body and play important roles in development and physiology. Defects of primary cilia cause a broad class of human genetic diseases called ciliopathies. To gain new insights into ciliary functions and better understand the molecular mechanisms underlying ciliopathies, it is of high importance to generate a catalog of primary cilia protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
208
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(226 citation statements)
references
References 38 publications
13
208
0
3
Order By: Relevance
“…A combination of proteomic, bioinformatic and genomic approaches (Ostrowski et al, 2002;Avidor-Reiss et al, 2004;Li et al, 2004;Keller et al, 2005;Kilburn et al, 2007;McClintock et al, 2008;Keller et al, 2009;Jakobsen et al, 2011;Hoh et al, 2012;Ishikawa et al, 2012) has identified many centrosome and cilium proteins. The centriole proteomes of Chlamydomonas (Keller et al, 2005) and Tetrahymena (Kilburn et al, 2007) have been analyzed, but direct proteomic analysis of mammalian centrioles has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of proteomic, bioinformatic and genomic approaches (Ostrowski et al, 2002;Avidor-Reiss et al, 2004;Li et al, 2004;Keller et al, 2005;Kilburn et al, 2007;McClintock et al, 2008;Keller et al, 2009;Jakobsen et al, 2011;Hoh et al, 2012;Ishikawa et al, 2012) has identified many centrosome and cilium proteins. The centriole proteomes of Chlamydomonas (Keller et al, 2005) and Tetrahymena (Kilburn et al, 2007) have been analyzed, but direct proteomic analysis of mammalian centrioles has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PC2 is considered as an endoplasmic reticulum (ER)-resident protein where it might also mediate Ca 2+ release from ER (Koulen et al, 2002). To date, proteomic studies have revealed the presence of hundreds of polypeptides inside the cilium (Gherman et al, 2006;Ishikawa et al, 2012). The mechanism by which these proteins are targeted to cilia, however, remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hypogonadotropic hypogonadism is a typical clinical feature of Bardet-Biedl syndrome, a human ciliopathy. Another putative link is suggested by the finding that WDR11, which is mutated in patients with hypogonadotropic hypogonadism (52), is present within primary cilia (53). However, our results indicate that disruption of GnRH neuronal cilia structure is not sufficient to prevent normal sexual maturation in mice.…”
Section: Discussionmentioning
confidence: 57%